Common Respiratory Disorders and their Management in Equines: An Overview - Narang, Asmita; Preet, Gurpreet Singh; Randhawa, Swaran Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Respiratory issues significantly impact horses, affecting performance and their overall health. Factors like weather, stress from racing, and exposure to irritants contribute to upper and lower respiratory tract problems. Nasal breathing and the lengthy nasopharynx of horses predispose them to airborne irritants. Diseases like nasal polyps, ethmoid hematomas, sinusitis, guttural pouch diseases, laryngeal issues, and pneumonia affect horses across ages and breeds, leading to symptoms such as nasal discharge, breathing difficulties, and exercise intolerance. Diagnosis often involves endoscopy, radiography, and cytology. Treatment varies from surgical interventions to environmental modifications, emphasizing early detection for effective management. Understanding the complexity of these respiratory disorders enables targeted strategies to safeguard the health and performance of horses.